UPAYA ORANG TUA DALAM MENGATASI REMAJA BERPERILAKU MENYIMPANG - Erida Erida (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Adolescence is a transition period taken by a person from childhood to adulthood. The situation of adolescents during this transition period tends to be unstable and shaky and much influenced by circumstances, situations, and social environment. Teenagers often do not have mental and mental preparation in dealing with all the problems and difficulties that arise in their lives, of course it will endanger themselves. In late adolescence began to arise interest in careers, sexuality and looking for his identity. Teenagers are the foundation of the nation's hope, the successor of the struggle, as well as the ongoing and ongoing development progress. Teenagers are tasked to equip themselves for a happy life, in association teenagers should have a good personality. During this period, adolescents experience personality formation, so they need guidance, especially from their parents so that teenagers' personalities are well formed according to their phases.